2019
DOI: 10.3390/sym12010020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Inference for the Weibull Distribution Based on δ-Record Data

Abstract: We consider the maximum likelihood and Bayesian estimation of parameters and prediction of future records of the Weibull distribution from δ -record data, which consists of records and near-records. We discuss existence, consistency and numerical computation of estimators and predictors. The performance of the proposed methodology is assessed by Montecarlo simulations and the analysis of monthly rainfall series. Our conclusion is that inferences for the Weibull model, based on δ -record data, clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our results open the door to the use of δ-records for statistical applications in the LDM. It has been shown that δ-records perform better than records in statistical inference, using trend-free data [44][45][46], so we expect that their use in the LDM is also advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results open the door to the use of δ-records for statistical applications in the LDM. It has been shown that δ-records perform better than records in statistical inference, using trend-free data [44][45][46], so we expect that their use in the LDM is also advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…setting, the distribution [41,42], process structure [43] and asymptotic properties [44] of δ-records have been studied. In the case δ < 0, where δ-records are more numerous than records, their use in statistical inference has been recently proposed and positively assessed; see [44][45][46]. In these articles, it is shown how the information of δ-records can be incorporated successfully into the likelihood of the sample, which is used for computing maximum likelihood and Bayes estimators and predictions of future records.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-records were introduced in [5] for applications in finance, and their properties were analysed in [6,7]. In addition, the related concept of the δ-record was introduced in [8] and later studied in [9][10][11][12]. These objects have practical applications in the case of negative δ, since δ-records are more numerous than records.…”
Section: Introductionmentioning
confidence: 99%
“…So, by considering samples of δ-records for statistical inference, we address the problem of the scarcity of records while keeping the extremal nature of the data. Indeed, it has been shown in [9] and in references therein that inferences based on δ-records outperform those based on records only.…”
Section: Introductionmentioning
confidence: 99%